Karakteristik Bayi Baru Lahir dari Ibu Terkonfirmasi COVID-19 - Manggiasih Dwiayu Larasati; Titin Nurmaningsih (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Corona Virus Disease 2019 (COVID-19) is a pandemic that began in the city of Wuhan in December 2019 and spread rapidly globally and has not ended until now. The COVID -19 infection is very deadly and no age is immune to the infection. Elderly people, pregnant women and newborns are the age group vulnerable to COVID -19 infection. Studies conducted so far have not revealed anything about vertical transmission of COVID -19 from mother to neonatus. The purpose of this study was to determine the characteristics of neonatus from mothers with confirmed COVID -19. The research method uses a retrospective principle with a cross sectional approach, the number of samples is 59 newborns from mothers with confirmed COVID -19. The results showed that there were only 4 babies (6.8%) who tested positive for mothers with confirmed COVID -19. The characteristics of newborns from mothers with confirmed COVID -19 are 31 neonatus (52.5%) are female, 46 neonatus (78%) have a normal weight between 2500-4000 grams, the majority of neonatus are born at a normal gestational age between 37-40 weeks, as many as 50 neonatus (84.7%) and most of them were born by cesarean section as many as 44 neonatus (74.6%). In general, newborns are able to adapt well, as indicated by the APGAR values in the first and fifth minutes including the normal category and no babies in the heavy category. However, almost all babies born to mothers with confirmed COVID-19 were given formula milk, namely 58 neonatus (98.3%). Therefore, it is hoped that it can be taken into consideration for leaders at research sites and related to be able to facilitate exclusive breastfeeding for newborns from mothers with confirmed COVID-19 while still implementing health protocols and considering the clinical conditions of mothers and neonatus because until now there are no reports that prove that COVID -19 can be transmitted through breastfeeding. The author also suggests that further research can be done to prove whether there is vertical transmission from mother to neonatus.